3D cell-based biosensors in drug discovery programs : microtissue engineering for high throughput screening - Kisaalita, William Ssempa, 1953- (Boca Raton : CRC Press, 2010)
'This book is based upon cutting-edge research conducted in the authors lab (Cellular Bioengineering), which over the past decade has developed a number of sophisticated techniques to facilitate use of 3D cell based assays or biosensors. This book uses data from peer-reviewed publications to conclusively justify use of 3D cell cultures in cell-based biosensors (assays) for (HTS). The majority of assays performed in accelerated drug discovery processes are biochemical in nature, but there is a growing demand for live cell-based assays. Unlike biochemical ones, cellular assays are functional approximations of in vivo biological conditions and can provide more biologically relevant information'--Provided by publisher.
Biosensors and bioassays -- Target-driven drug discovery -- Comparative transcriptional profiling and proteomics -- Comparative structure and function -- Chemical microenvironmental factors -- Spatial and temporal microenvironmental factors -- Material physical property and force microenvironmental factors -- Proteomics as a promising tool in the search for 3D biomarkers -- Readout present and near future -- Ready-to-use commercial 3D plates -- Challenges to adopting 3D cultures in HTS programs -- Cases for 3D cultures in drug discovery -- Ideal case study design.
Keywords: Biosensing Techniques -- methods; Cells, Cultured; Drug Discovery